Totally chlorine-free bleaching of soda rapeseed pulp - Říhová, Martina; Potůček, František (Slovenská spoločnosť chemického inžinierstva, 2017)
Laboratory bleaching study was carried out on soda rapeseed pulp to investigate the influence of two bleaching oxidisers, namely hydrogen peroxide and peracetic acid, on pulp properties. The five-stage bleaching sequence, Q1Q2EPPaaP, containing two chelation stages, as well as alkaline extraction, was selected for totally chlorine-free bleaching process. The brightness and zero-span tensile index of bleached pulps were measured after the EP, Paa, and P stages. The results obtained showed that totally chlorine-free bleaching did not bring the sufficient bleaching effect for soda pulp cooked from rapeseed straw.
TCF bělení natronové buničiny z řepkové slámy
Keywords: soda rapeseed pulp; bleaching; brightness; zero-span breaking length; natronová řepková buničina; bělení; bělost; tržná délka vláken